2022
DOI: 10.2147/dddt.s358042
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dexmedetomidine in Tumor-Progressive Factors in the Perioperative Period and Cancer Recurrence: A Narrative Review

Abstract: Dexmedetomidine, a specific α2 adrenergic receptor agonist, is highly frequently used in the perioperatively for its favorable pharmacology, such as mitigating postoperative cognitive dysfunction. Increasing attention has been recently focused on the effect of whether dexmedetomidine influences cancer recurrence, which urges the discussion of the role of dexmedetomidine in tumor-progressive factors. The pharmacologic characteristics of dexmedetomidine, the tumor-progressive factors in the perioperative period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“… Chen et al (2020) reported that Dexmedetomidine suppresses or induces immune cell functions, implying better expression. One study reported that Dexmedetomidine somewhat reduces the magnitude of immune function suppression, giving way to cancer development ( Cai et al, 2022 ). The expression of peripheral immune cells is the downside of Dexmedetomidine among primary liver cancer patients undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Chen et al (2020) reported that Dexmedetomidine suppresses or induces immune cell functions, implying better expression. One study reported that Dexmedetomidine somewhat reduces the magnitude of immune function suppression, giving way to cancer development ( Cai et al, 2022 ). The expression of peripheral immune cells is the downside of Dexmedetomidine among primary liver cancer patients undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of proinflammatory cytokine and chemokines (interleukin-2) is detrimental among primary liver cancer patients who have undergone hepatectomy ( Sachdeva et al, 2015 ; Sachdeva and Arora, 2020 ; Cai et al, 2022 ; Chen et al, 2022 ; Lu et al, 2022 ). From the observations above, we could conclude that Dexmedetomidine could be a potential agent against the progression of primary liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, DEX regulates the malignant phenotype of breast cancer cells 7 and ovarian cancer cells 8 in vivo and in vitro. Importantly, it has been confirmed that DEX exhibits different roles in cell biological behavior depending on cancer cell types 9 . Previous studies on DEX in GC have mostly focused on clinical aspects.…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, it has been confirmed that DEX exhibits different roles in cell biological behavior depending on cancer cell types. 9 Previous studies on DEX in GC have mostly focused on clinical aspects. Studies on DEX on postoperative analgesia and cellular immune function, 10 and postoperative cognitive function 5 in patients undergoing radical gastric cancer surgery have confirmed the safety of DEX anesthesia in surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Another clinical trial showed that the elderly patients in ICU impacting of DEX increase the 2-year survival rate postoperatively [ 15 ]. The application of DEX has also been implied to influence oncological prognosis [ 16 ]. Despite the possible beneficial effects of DEX on perioperative patients, its role in pancreatic cancer surgery has not been well established.…”
Section: Introductionmentioning
confidence: 99%